Associations between obesity and sociodemographic, behavioral, and health characteristics in a population of women: a population-based study in Vitória, Espirito Santo, Brazil - Nathália Miguel Teixeira Santana; Franciéle Marabotti Costa Leite (Frontiers in Public Health)
IntroductionObesity is a significant public health concern, with its prevalence rising in many countries worldwide. Studies have shown that women are more likely to become obese than men. This article aimed to describe the nutritional status of women, determine the prevalence of obesity, and explore its associations with sociodemographic, behavioral, and health characteristics.MethodsThis cross-sectional, analytical, population-based study was conducted in Vitória, Espírito Santo, Brazil. It included women 18 years and older. Obesity was assessed based on self-reported weight and height and was classified according to the body mass index (BMI). Women were classified as obese (BMI ≥ 30 kg/m2) and non-obese (BMI ≥ 18.5 and <30 kg/m2). All analyses were conducted using Stata® 14.0 software.ResultsAmong the women studied, 3% were underweight [N = 32; 95% confidence interval (CI) 0.02–0.04], 41.8% were normal weight (N = 449; 95% CI 0.39–0.45), 33.2% were overweight (N = 356; 95% CI 0.30–0.36), and 22% were obese (N = 236; 95% CI 0.20–0.25). The prevalence of obesity was higher among women aged 30–39 years (27.6%), those with 0–8 years of education (33.9%), those in the lowest tertile of family income (30.5%), those who engaged in physical activity (26.7%), women with five or more pregnancies (39.7%), and those with diabetes (35.2%), hypertension (34.8%), and depression (29.7%) (p < 0.05). We found a significant association between obesity and all older age groups compared to the youngest one (18-29), except for women aged 60 or older (p = 0.004), who had a higher prevalence of obesity. Lower categories of education and family income registered almost twice the prevalence of obesity (prevalence ratio [PR]:1.70; 95%CI 1.21–2.38; p < 0.009 and PR: 2.00; 95%CI 1.36–2.95; p < 0.002) compared to those in the highest categories. Additionally, having five or more pregnancies was associated with an increased probability of obesity (PR: 1.66; 95%CI 1.04–2.64; p = 0.002). The presence of diabetes (PR: 1.34; 95%CI 1.03–1.74), hypertension (PR: 1.56; 95%CI 1.21–2.00), and depression (PR: 1.44; 95%CI 1.13–1.83) was also significantly associated with obesity compared to women without these diseases (p < 0.05).ConclusionOur findings indicate that obesity is significantly associated with age, family income, education level, number of pregnancies, and chronic diseases, including diabetes, hypertension, and depression.